Practitioner research in the practice and education of healthcare professionals in the netherlands (Texto & Contexto, 2019)
Objective: the purpose of this study is to explore the increased attention for practitioner research in the practice of healthcare professionals in the Netherlands and its consequences for the implementation of research in higher professional healthcare education. Method: this study is a reflection based on a literature review. Results: recent developments in the practice of healthcare professionals in the Netherlands have led to the belief that an analytic, inquisitive and reflective capacity is playing an increasingly important role for healthcare professionals to function optimally and to improve clinical practice through innovation. In the Netherlands professionals in healthcare carry out practitioner research projects to construct local knowledge and improve their own professional practice. Increasingly, institutes for higher professional healthcare education have implemented continuous research curricular strands to teach students to conduct practitioner research. Conclusion: practitioner research is seen as an effective professional learning strategy that promotes the use of theory and recognizes practical knowledge and expertise of the healthcare professionals and their patients and clients. Practitioner research should be implemented in practice and education as a distinct form of research. In continuous research curricular strands in higher professional healthcare education students should acquire sufficient research self-efficacy and the experience that practitioner research can enhance professional learning and practice development